2010
DOI: 10.4209/aaqr.2010.03.0020
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Identification of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans in the Ambient Central Taiwan

Abstract: Polychlorinated Dibenzo-p-dioxins and Dibenzofurans (PCDD/Fs) in the ambient air of five sampling sites around central Taiwan were investigated. Principal components analysis (PCA), cluster analysis (CA) and the chemical mass balance (CMB) model were adopted to assess possible PCDD/F sources and their effects on the air quality levels. Field experimental results showed that the mean PCDD/F concentrations in the ambient air were 0.0526, 0.0591, 0.0339 and 0.0727 pg I-TEQ/Nm 3 in winter, spring, summer and autum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Widespread burning of joss paper, some of which is burnt out in the open, occurs on the first and fifteenth day of every month (according to lunar calendar) and on important Chinese festivals. The burning of joss paper, wood, and agricultural wastes has been demonstrated to significantly create particulate matter (PM) (Fang et al, 2003;Choosong et al, 2010;Ning and Sioutas, 2010;Li et al, 2010), metals (Lau and Luk, 2001;Fang et al, 2003), polycyclic aromatic hydrocarbons (PAHs) (Yang et al, 2005;Lin et al, 2008;Rau et al, 2008), and polychlorinated dibenzo-p-dioxin/ dibenzofurans (PCDD/Fs) (Hu et al, 2009;Wu et al, 2010;Chiu et al, 2011;Lin et al, 2011). Furthermore, PAHs concentrations in ambient air during festivals were observed to be several times higher than those during other times .…”
Section: Introductionmentioning
confidence: 99%
“…Widespread burning of joss paper, some of which is burnt out in the open, occurs on the first and fifteenth day of every month (according to lunar calendar) and on important Chinese festivals. The burning of joss paper, wood, and agricultural wastes has been demonstrated to significantly create particulate matter (PM) (Fang et al, 2003;Choosong et al, 2010;Ning and Sioutas, 2010;Li et al, 2010), metals (Lau and Luk, 2001;Fang et al, 2003), polycyclic aromatic hydrocarbons (PAHs) (Yang et al, 2005;Lin et al, 2008;Rau et al, 2008), and polychlorinated dibenzo-p-dioxin/ dibenzofurans (PCDD/Fs) (Hu et al, 2009;Wu et al, 2010;Chiu et al, 2011;Lin et al, 2011). Furthermore, PAHs concentrations in ambient air during festivals were observed to be several times higher than those during other times .…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, our previous study (Chang et al, 2003) also indicated that the atmospheric PCDD/F concentrations measured in the vicinity of municipal waste incinerators in northern Taiwan ranged from 56.0 to 348 fg I-TEQ/m 3 . Other relevant studies (Hsieh et al, 2009;Wu et al, 2010b) have also indicated that atmospheric PCDD/F concentrations measured in industrial parks in central and southern Taiwan range from 33.9 to 72.7 fg I-TEQ/m 3 and 19.0 to 165 fg I-TEQ/m 3 , respectively. In other Asian countries such as Korea and Japan, the atmospheric PCDD/F concentrations in urban areas have been shown to range from 28 to 120 fg I-TEQ/m 3 (Makiya, 1999;Lee et al, 2007), which are similar to another of our previous studies (Chi et al, 2008a) where we measured atmospheric PCDD/F concentrations in an urban area of Taiwan to be in the range 20 to 110 fg I-TEQ/m 3 .…”
Section: Variation In Ambient Pcdd/f Concentrations In Northern Taiwamentioning
confidence: 99%
“…PCDD/Fs were first found in the fly ash of a municipal solid waste incinerator (MSWI) (Olie et al, 1977). Since then, attention has been paid on many other emissions sources by environmental science researchers (Wang et al, 2003;Lee et al, 2004;Kao et al, 2006;Hu et al, 2009;Lin et al, 2010b;Chuang et al, 2010aChuang et al, , 2010bWang et al, 2010aWang et al, , 2010bWu et al, 2010;Yu et al, 2010;Chiu et al, 2011; * Correspondence author. Tel: +886-6-2353535 ext.…”
Section: Introductionmentioning
confidence: 99%